(untitled) (AYUSHDHARA, 2020)
The principles and practices in relation to human health as described in Ayurveda signify the moulding techniques of inculcating healthy personality in dependence of Kala or the time. The Kala is accepted as one of the important environmental phenomena from the health and disease point of view. The life style prescribed in Ayurveda according to Kala plays a vital role in maintaining and promoting the positive health as well as to prevent and cure the diseases. Dosha, Agni, Bala, Ahara, Vyadhi, Oushadha and Chikitsa etc various factors are influenced by Kala. Ageing also depends upon the Kaala which helps us to ascertain the Sharira Avastha, Sharira bala and Roga bala etc of the person according to which the treatment can be planned to reduce the sufferings of the patient. So here, an effort is made to elucidate the therapeutic application of Kaala or the time in reference to Panchakarma therapies that does the Kaya Shodhana which can be considered as the detoxification or purification of the body.